Integration of Electronic Music Looping in Orchestra as an Innovative Teaching Resource - Sari, Ayuthia Mayang; Ferdian, Robby; Hidayat, Hengki Armez; Putra, Irdhan Epria Darma; Achour, Zyed; Avila, Flor Amara (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study introduces an innovative approach to orchestral education by blending classical music principles with popular music elements and electronic looping technology. In a landscape where classical music often struggles to captivate students drawn to contemporary genres, this approach aims to maintain classical music's discipline while delivering a dynamic and engaging learning experience. The research evaluates student responses to the use of looping technology, examining its impact on learning outcomes and identifying associated benefits and challenges. A mixed-methods approach was employed, involving 37 students from an orchestral course at Universitas Negeri Padang. Data were collected through questionnaires, semi-structured interviews, and observations over one semester. The results reveal that electronic looping technology significantly enhances student interest and engagement, offering a fresh perspective on orchestral practice. The technology not only bridges classical and modern musical expressions but also facilitates individualized learning, enabling students to explore creativity within structured compositions. Most participants demonstrated a higher interest in repertoires incorporating looping technology than in traditional classical pieces. Furthermore, the integration of partiture-based learning with digital tools improved students' technical skills, rhythmic accuracy, and ensemble cohesion. However, challenges related to synchronization and technical setup highlight the need for targeted instructional strategies and technological support. The novelty of this study lies in its exploration of how digital tools like looping technology can revitalize classical music education, making it more relevant to today's students. These findings offer practical insights for music educators seeking to innovate teaching methods and adapt to the evolving digital landscape in education.